Polar Perturbations in Functional Oxide Heterostructures - Oh, Yoon Seok; Wang, Lingfei; Lee, Hyungwoo; Choi, Woo Seok; Kim, Tae Heon (Advanced Functional Materials, 2023)
Growth and characterization of metal-oxide thin films foster successful development of oxide-material-integrated thin-film devices represented by metal-oxide-semiconductor field-effect transistors (MOSFET), drawing enormous technological and scientific interest for several decades. In recent years, functional oxide heterostructures have demonstrated remarkable achievements in modern technologies and provided deeper insights into condensed-matter physics and materials science owing to their versatile tunability and selective amplification of the functionalities. One of the most critical aspects of their physical properties is the polar perturbation stemming from the ionic framework of an oxide. By engineering and exploiting the structural, electrical, magnetic, and optical characteristics through various routes, numerous perceptive studies have clearly shown how polar perturbations advance functionalities or drive exotic physical phenomena in complex oxide heterostructures. In this review, both intrinsic (engraved by thin-film heteroepitaxy) and extrinsic (reversibly controllable defect-mediated disorder and polar adsorbates) elements of polar perturbations, highlighting their abilities for the development of highly tunable functional properties are summarized. Scientifically, the recent approaches of polar perturbations render one to consolidate a prospect of atomic-level manipulation of polar order in epitaxial oxide thin films. Technologically, this review also offers useful guidelines for rational design to heterogeneously integrated oxide-based multi-functional devices with high performances.
Keywords: Complex oxides; Functional oxides; Functionality; Metal oxide thin films; Metaloxide semiconductor field-effect transistor (MOSFETs); Oxide heterostructures; Oxide materials; Polar perturbation; Thin-film devices; Thin-films; complex oxides; functionalities; heteroepitaxy; polar perturbations; thin films